First record of Pudeoniscidae Lemos de Castro, 1973 (Oniscidea) from Peru, with the description of a new genus and species - Ocampo-Maceda, Ana Teresa; López-Orozco, Carlos Mario; López-Tejeda, Evaristo Luciano; Campos-Filho, Ivanklin Soares (European Journal of Taxonomy, 2023)
A new genus of Pudeoniscidae from Peru is described, Loretoniscus gen. nov., including a new species: Loretoniscus mashiriaensis gen. et sp. nov. The new genus is characterized by pereonite 1 epimera without dorsolateral furrows, pereonites 1 and 2 without ventral lobes, telson with distal portion covering uropod endopods, and pleopod 1–2 exopods with respiratory areas. This is the first record of the family Pudeoniscidae from Peru, considerably extending its distribution in the Neotropical region.